2009
DOI: 10.1016/j.jmaa.2008.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of some block operator matrices and application to transport operators

Abstract: In this paper a new concept for a 3 × 3 block operator matrix is studied on a Banach space.It is shown that, under certain conditions, it defines a closable operator and its essential spectra are determined. Application to transport operators in L 1 -space is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 16 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…This together with Lemma 4.2-(ii), Proposition 2 in [9] and Eq. (9), make us conclude that (11) G(λ)(S λ − λM 4 ) −1 := G(λ)(T…”
Section: Application To Two-group Transport Equationsmentioning
confidence: 77%
See 2 more Smart Citations
“…This together with Lemma 4.2-(ii), Proposition 2 in [9] and Eq. (9), make us conclude that (11) G(λ)(S λ − λM 4 ) −1 := G(λ)(T…”
Section: Application To Two-group Transport Equationsmentioning
confidence: 77%
“…In this direction some issues may be found in the literature, we can quote for example [1,2,10,16,24]. Recently, an account research and a wide panorama of methods to investigate the spectral theory of block operator matrices is given in [3,4,5,11,14,25]. More precisely, the description of various essential spectra of a block operator matrix L appears in [3,5,11,14] to improve and generalize some results given by [1,2,24] for block operator matrices in Banach spaces under some compactness assumptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [20], Moalla, Damak and Jeribi extended these results to a large class of operators, described their essential spectra, and applied these results to describe the essential spectra of two-group transport operators with general boundary conditions in L p -spaces. In [16], Jeribi, Moalla and Walha treated a 3 × 3 block operator matrix (1.1) on a Banach space. It was shown that under certain conditions, this block operator matrix defines a closable operator and its essential spectra are determined.…”
Section: Introductionmentioning
confidence: 99%
“…Essential spectra of some matrix operators on Banach spaces (see [1]) and spectra of some block operator matrices (see [2]) were investigated, with applications to differential and transport operators. This paper investigates the variations of the unit spectrum as T varies over the space of all bounded operator on the Banach space…”
mentioning
confidence: 99%